Combined Application of Honokiol and 2-Deoxyglucose against MCF7 Breast Cancer Cells Under Hypoxia - Alexander M. Scherbakov; Ekaterina Igorevna Mikhaevich; Alexandra L. Mikhaylova; Danila V. Sorokin (Engineering Proceedings, 2023)
Breast cancer is the most common cancer among women. Epidemiologists estimate that over 2.3 million new cases of breast cancer are diagnosed worldwide each year. Natural compounds represent promising molecules for the development of antitumor drugs; among them, lignans show significant antiproliferative effects against breast cancer cells. The goal of the study was to analyse the antiproliferative effects of lignan honokiol on MCF7 breast cancer cells, find synergistic combinations of honokiol with 2-deoxyglucose, and evaluate the effects of the combinations found on cells in hypoxia. The antiproliferative effects of the compounds were evaluated by the MTT test, and protein expression analysis was performed by immunoblotting. Honokiol inhibited MCF7 cell growth with an IC50 value of 19.7 μM. Synergistic combinations of honokiol with the glycolysis inhibitor 2-deoxyglucose were detected; the compounds at low doses caused significant suppression of MCF7 cell growth. The established combinations of compounds inhibited HIF-1α expression and were effective in hypoxia, considered as the leading factor of chemotherapeutic resistance. Oestrogen receptor alpha (ERα) is the main growth driver of hormone-dependent breast tumours. Honokiol combined with 2-deoxyglucose reduced ERα expression in MCF7 cells, and expression of the hormone-dependent protein GREB1 was also downregulated. Honokiol at a concentration of 15 μM in combination with 6 mM 2-deoxyglucose induced the cleavage of PARP (a marker of apoptosis) in MCF7 cells after 48 h of incubation. The cells treated with the combination of honokiol and 2-deoxyglucose demonstrated a decrease in the expression of cyclin D1. Thus, honokiol represents a promising basis for the development of antitumor agents; the combination of this natural compound with glycolysis inhibitors can be used to reduce the applied doses.